Perspectives on Identity and d/Deaf and Hard-of-Hearing Students - Elaine R. Smolen; Peter V. Paul (Education Sciences, 2023)
The present narrative synthesis summarizes perspectives on the development of identity, or a sense of self, and the intersectionality of salient factors related to individuals who are d/Deaf and hard of hearing. Prior research indicates that identity encompasses the stories of an individual’s experiences and relationships; identity development may not be static but rather dynamic and ongoing throughout an individual’s lifetime. After this general background, the article focuses on identity and deafness, particularly for children in K-12 educational settings. There are a multitude of factors—physiological (e.g., hearing acuity, appearance, gender), psychological (e.g., memory, intelligence, affective behaviors), and social (e.g., education, home or immigrated environment, ethnicity, group membership)—that contribute to the development of identity. This discussion is based on a synthesis of a variety of published sources; however, as much as possible, the focus is on empirical research conducted with children and young adults who are d/Deaf and hard of hearing. Results of the narrative synthesis suggest several topics around which the extant research coalesce: traditional and evolving views of d/Dhh identity, d/Dhh identity as fluid, identity development through relationships, identity and children with cochlear implants and those who are hard of hearing, the role of educational experiences, and intersectional identity development. The article concludes with a summary and recommendations for further investigation.